Słów kilka o mistrzu pokonanej rozpaczy - Sabo, Roman (Postscriptum Polonistyczne, 2020)
Why does Miłosz so often suggest in his poetry that he has concealed something essential from his readers? What is the intended meaning of the frequent phrase of Miłosz’s: if only I told you all about myself? Why this persistent reference to some unnamed feature, truth, wisdom, revelation? Is this, as some critics tend to believe, a part of a creative strategy, some sort of a subversive play with the reader? Is this a strategy employed in order to create a dark counterargument to luminous poetry of grateful existence? Or is it, as the author of the article suggests, a deliberate strategy to entice the reader to undertake a meticulous contemplation of Miłosz’s attitude towards the social function of poetry? Sabo suggests that Miłosz, who due to historical and social reasons, put so much stress on the utility aspect of the poetic vocation, was actually a poet who was most interested in a pure poetry unyoked from any specific cause, except the cause of relentless expression of gratitude.